Black sickle cell patients' lives matter: healthcare, long-term shielding and psychological distress during a racialised pandemic in England – a mixed-methods study. Issue 9 (23rd September 2022) - Berghs, Maria J; Horne, Francesca; Yates, Scott; Graham, Sadeh; Kemp, Rachel; Webster, Amy; Howson, Carlton
Abstract : Objective: To understand the psychological and social impact of shielding on people with sickle cell disorders and their carers in the Midlands region of England. This region was badly affected during the pandemic, with the city of Birmingham having some of the highest rates of COVID-19 deaths. Design: A mixed-methods project with a quantitative survey on shielding and adapted SF36 V.2 questionnaire, which was supplemented by qualitative semistructured interviews analysed using interpretive phenomenological analysis (IPA). Participants: Fifty-one participants who were predominantly of Black Caribbean or Black African heritage anonymously took part in the online survey. We supplemented this with eight in-depth semistructured interviews with adults with sickle cell disorders using IPA. Results: The adapted 36-Item Short Form Survey (SF36) version 2 (V. 2) survey indicated worse quality of life and mental health. The open-ended questions from the adapted survey also identified shielding concerns about hospital care, pain management and knowledge of sickle cell by healthcare professionals. From the interviews, it emerged that the racialised element of the pandemic caused significant psychological distress for a population group that had to regularly access hospitals. It was noted that psychological health needs both during a pandemic and outside of it were poorly understood and became invisible in services. The psychological impact of experiences of hospital care as well as growing up with an invisible chronic condition were important to understand psychologically.